(untitled) (Journal of the College of Basic Education, 2023)
Through my readings in the sources of Arabic literature and its references, past and present, I found that most of the criticsThe scholars believe that al-Akhtal was imitating the pre-Islamic poets, especially al-Nabigha al-Dhubiani and al-Asha inHis poetry, especially in his praises. Indeed, he surpassed Arab poets in his praise of kings.which developed a lot during the Umayyad era.His praises were a source of admiration for the praised caliphs, governors and princes.From this point of view, I decided to research the topic (the structure of the artistic poem of praise at the time of error).To verify the validity of what has been said about this poet, did he develop the structure of the pre-Islamic praise poem or did he follow the same path?The approach of the pre-Islamic poets and trace their footsteps? What is new that he brought to constitute a new addition to the poemPraise can be recorded for this poet, the stallion that Ibn Salam placed in the first class of poets.Islamists?